Analisis Kejelasan Dan Kelengkapan Teks Petunjuk Denah Pada Karangan Siswa Kelas VIII Di SMP Negeri 2 Sawit Boyolali - Susanti, Heni, Prof. Dr. Markhamah, M. Hum (2016)
This study aimed to analyze the completeness and clarity of text instructions on the composition sketch eighth grade students at SMP Negeri 2 Sawit. The data used in this study is the composition students of SMP Negeri 2 Sawit. The data collection technique used is the technique of documentation. Data analysis method used is the method agih followed by insertion technique, expansion, and dressing. The results of this study are as follows. (1) Based on the analysis of the completeness of the number of sentences and the completeness of the plan of 15 discourse, there are 11 discourse incomplete and 4 discourse incomplete. (2) Based on an analysis of clarity sentence of 15 discourse, there are two discourses have a clear sentence, 3 discourse in which there is less clear sentences and 10 sentences of discourse in which there are not clear. Keywords: discourse, sentence, completeness and clarity.